In vitro morphological studies and cultural characterization of Pestalotiopsis Sp. associated with Nepenthes truncata macf. - Bongcawil, Roxanne Yen C. (2007)
A fungus pestalotiopsis sp. from brown leafspot-infected pitcher plants (Nephentes truncate macf.) in Marilog District, Davao City was isolated to pure culture. Fungus growth in plated Potato Dextrose Agar (PDA) appeared white and cottony with punctiform acervuli. Under microscopy, the fungus hypha is hyaline, septated with hyphal cells measuring 23.99 (1.40)m wide. The conidia, which define the genius, are fusiform with 3 yellowish-brown median cells and hyaline appendages at opposite ends. The basal portion having 1 and the apical portion with 2 to 3 appendages. Total spore size is 22.09 ((1.73)m long and 6.11 (0.64)m wide. The 3 median cells measured 15 (1.17)m long. The basal appendage is 5.04 (1.69)m long while the apical appendages ranged from 9.54 to 34.09m, with an average of 20.41 (6.35)m ling. In axenic PDA medium, cultures grown under alternating 12-hr light and 12-hr darkness had the widest colonies, however, spore production was highest with continuous light after a 7-day growth time. No spore was observed on cultures under continuous darkness. Colony growth was widest and spore production highest with cultures under pH 8. Mycelial growth was not significantly influenced by culture temperatures, 230C and 27oC, however, spore production was higher in the former